Evaluating Learners’ Satisfaction Following Perioperative Nursing Simulation Training - Whelan, Trish; Shi, Xinzhe; Andony, Keith; Yorke, Sue; Poonai, Susan (Operating Room Nurses Association of Canada Journal, 2018)
From January 2015 to July 2016 five cohorts, comprising 24 Registered Nurses and 22 Licensed Practical Nurses, from Alberta Health Services and Covenant Health in Edmonton, AB, successfully completed the AHS Perioperative Nursing Simulation Labs provided through the Centre for the Advancement of Minimally Invasive Surgery (CAMIS). All learners’ experiences were selfevaluated in the areas of instruction, facilities, instruments, and usefulness. The evaluations indicated a high level of learner satisfaction that indicated the simulation training was effective and useful in enhancing the competency, confidence, and communication skills of novice perioperative nurses.